No-reference image quality assessment based on spatial and spectral entropies - Liu, Lixiong; Liu, Bao; Huang, Hua; Bovik, Alan Conrad (Signal processing. Image communication, 2014)
We develop an efficient general-purpose no-reference (NR) image quality assessment (IQA) model that utilizes local spatial and spectral entropy features on distorted images. Using a 2-stage framework of distortion classification followed by quality assessment, we utilize a support vector machine (SVM) to train an image distortion and quality prediction engine. The resulting algorithm, dubbed Spatial–Spectral Entropy-based Quality (SSEQ) index, is capable of assessing the quality of a distorted image across multiple distortion categories. We explain the entropy features used and their relevance to perception and thoroughly evaluate the algorithm on the LIVE IQA database. We find that SSEQ matches well with human subjective opinions of image quality, and is statistically superior to the full-reference (FR) IQA algorithm SSIM and several top-performing NR IQA methods: BIQI, DIIVINE, and BLIINDS-II. SSEQ has a considerably low complexity. We also tested SSEQ on the TID2008 database to ascertain whether it has performance that is database independent. •SSEQ extracts a 12-dimensional local entropy feature vector from the inputs.•SSEQ correlates highly with the human subjective impressions of image quality.•SSEQ has a relatively low time complexity.